KONSEP IMPLEMENTASI PENANAMAN AKHLAK SISWA BERBASIS NILAI-NILAI ISLAM - Siti Amilus Soleha (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
At this modern era, the interaction of students cannot always be limited by some bulkheads. Interactivity can occur in any direction and at any time. Moral decadence always developed along with problem solved that had never ended. In the world of educational institutions, teachers have a very strategic and urgent position in fostering the morals of students. Moral in education is an effort made to provide guidance to students, so that their behavior is in accordance with Islamic guidance, so they can distinguish between good behavior and bad behavior. The morals that must be taught to students include morality to Allah SWT and morality to humans.